MXene-enhanced ePatch with antibacterial activity for wound healing - Feng, Jing; Liu, Rui; Yuan, Xuefeng; Cao, Changkui; Xie, Ji; Sun, Zhaorui; Ma, Sai; Nie, Shinan (Frontiers in Chemistry, 2023)
Prudent wound-healing strategies hold great potential in expediting tissue renovation and regeneration.Despite the widespread adoption of hydrogels as preferred carriers for wound healing patches, achieving optimal mechanical compatibility and superior wound performance remains a formidable challenge. Consequently, meticulous attention must be given to the formulation of hydrogel structure and materials design to overcome these hurdles. In response, we have developed an ePatch composed of polyacrylamide (PAAM) as the primary hydrogel structure, augmented with MXene, silver nanowires (AgNWs), and resveratrol to act as sustained-release agents, structural enhancers, and antibacterial agents, respectively. Notably, the ePatch exhibited exceptional wound-fitting capabilities and impressive mechanical stretchability (with a relative standard deviation [RSD] of only 1.36% after 55 stretches) and Young's modulus. In contrast to the commercial 3M Tegaderm, the ePatch demonstrated superior wound healing properties, with the inclusion of MXene into PAAM/AgNWs playing a pivotal role in expanding the ePatch's potential use across various interconnected fields.